2002
DOI: 10.1007/s00299-002-0565-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of haploids of neem (Azadirachta indica A. Juss.) by anther culture

Abstract: Androgenic haploids of the neem tree (Azadirachta indica A. Juss.) were produced by anther culture at the early-to late-uninucleate stage of pollen. Haploid formation occurred via callusing. The best medium for inducing callusing in the anther cultures was Murashige and Skoog's basal medium (MS) (9% sucrose) supplemented with 1 µM 2,4-D, 1 µM NAA and 5 µM BAP, while anther callus multiplied best on MS medium supplemented with 1 µM 2,4-D and 10 µM Kn. These calli differentiated shoots when transferred to a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…At the uninucleate stage, the wall of microspores is thin and it is easy to divert their mode of development from gametophytic to sporophytic. Androgenesis in Neem was earlier reported by Chaturvedi et al 7 from a tree growing at Delhi (North), India. However, as heterozygosity due to cross pollination and also the environmental conditions of the two regions have great influence on the physiology of parent plant, 8,9 consequently, nutritional requirements of the two plants may vary under the in vitro conditions.…”
Section: Resultssupporting
confidence: 61%
“…At the uninucleate stage, the wall of microspores is thin and it is easy to divert their mode of development from gametophytic to sporophytic. Androgenesis in Neem was earlier reported by Chaturvedi et al 7 from a tree growing at Delhi (North), India. However, as heterozygosity due to cross pollination and also the environmental conditions of the two regions have great influence on the physiology of parent plant, 8,9 consequently, nutritional requirements of the two plants may vary under the in vitro conditions.…”
Section: Resultssupporting
confidence: 61%
“…Sanyal et al, (1981) also reported that 5% sucrose gave the best callus initiation and growth when neem stem sections were inoculated on MS basal medium supplemented with different combinations of IAA (0.1-0.5 mg/l), BAP (0.1-0.5 mg/l) and sucrose (5%). Chaturvedi et al, (2003) obtained the best callus proliferation response from anthers on MS medium supplemented with 9% sucrose, 1.0 µM 2, 4-D, 1.0 µM NAA and 5.0 µM BAP. The percentage of anthers callused and amount of callusing were markedly better than 3.0% or 12.0% sucrose.…”
Section: Discussionmentioning
confidence: 97%
“…Chaicharoen et al (1996) observed maximum 9 shoot from callus, when medium was supplemented with 1.0 mg/l BA in Melia azedarach. Chaturvedi et al (2003) revealed that 5 µM BAP alone favored shoot induction from anther derived callus on MS medium. Srivastava et al (2009) observed maximum (78%) shoot regeneration when callus was sub cultured on MS medium containing 5 µM BAP alone in A. indica.…”
Section: Discussionmentioning
confidence: 99%